EFFECTS OF TANNIN COMPOUNDS ON 2 SPECIES OF COLLEMBOLA - POINSOTBALAGUER, N; RACON, L; SADAKA, N; LEPETIT, J (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1993)
The effects of condensed and hydrolysable tannin extracted from evergreen oak leaves (Quercus ilex L.) were tested on two species of Collembola. Concentrations lower than those present in the litter leaves were toxic to these insects. Detoxification by washing with rainwater and biodegradation of tannic compounds are necessary for litter decomposition, in which microarthropods participated, to occur.
Citation
Keywords: Collembola; evergreen oak; Tannins